The effect of atropine in preventing catheter-related pain and discomfort in patients undergoing transurethral resection due to bladder tumor; prospective randomized, controlled study - Şahiner, Yeliz (Korean J Pain, 2020)
BACKGROUND: Catheter-related bladder discomfort (CRBD) has been observed in many patients undergoing a urethral catheterization. CRBD may be so severe that the patients require additional analgesics. Muscarinic receptors are involved in the mechanism of CRBD. The aim of this study is to determine the effects of the antimuscarinic properties of atropine, which is frequently used in current practice on CRBD, by comparing it with sugammadex which has no antimuscarinic effects. METHODS: Sixty patients selected for transurethral resection due to bladder tumors were randomized into 2 groups: an atropine group and a sugammadex group, with no antimuscarinic effect. The patients were given rocuronium (0.6 mg/kg) as a neuromuscular-blocker. In addition to the frequency and severity of CRBD postoperatively at 0, 1, 6, 12, and 24 hours, postoperative numeric rating scale (NRS) scores, and postoperative nausea and vomiting were examined. RESULTS: The incidence of CRBD was significantly lower in the atropine group in all postoperative measurements. The score was found to be significantly lower in the atropine group when NRS measurements were performed at all time periods (P < 0.01). There was no difference between the groups in terms of nausea and vomiting (P > 0.05). CONCLUSIONS: Atropine is a cheap, easy-to-access, safe-to-use drug for reducing CRBD symptoms, without any observed adverse effects. Since it not only reduces CRBD symptoms but also has a positive effect on postoperative pain, it can be used safely to increase patient comfort in patients receiving general anesthesia and a urinary catheter.